Darwin wasps of the subfamily Pimplinae (Hymenoptera: Ichneumonidae) of Mexico: genera Apechthis Förster, Itoplectis Förster and Pimpla Fabricius - Khalaim, Andrey I.; Ruíz-Cancino, Enrique (Zootaxa, 2021)
Mexican species of three pimpline genera, Apechthis Förster (one  species), Itoplectis Förster (six species) and Pimpla Fabricius (20 species, including one unidentified taxon), are reviewed. Four species of Pimpla are described as new to science: P. chamela sp. nov., P. oaxacana sp. nov., P. tequila sp. nov. and P. xalapana sp. nov. Pimpla thoracica Morley, 1914 is found to be a junior synonym of P. ellopiae Harrington, 1892 (syn. nov.). Apechthis zapoteca (Cresson) is recorded for the first time from Venezuela, Pimpla dimidiata (Townes) from Mexico, P. caeruleata Cresson, P. croceiventris (Cresson), P. sanguinipes Cresson and P. sumichrasti Cresson from Honduras, P. ichneumoniformis Cresson and P. viridescens Morley from Guatemala and Honduras, and P. punicipes Cresson from Panama. The South American species Pimpla caerulea Brullé and the Nearctic species P. pedalis Cresson are excluded from the Mexican fauna. Male of Itoplectis mexicana and female of Pimpla dimidiata are recorded for the first time. Identification keys to the species of Itoplectis and Pimpla occurring in Mexico are provided.